2021
DOI: 10.1111/ajt.16461
|View full text |Cite
|
Sign up to set email alerts
|

Protection of liver sinusoids by intravenous administration of human Muse cells in a rat extra-small partial liver transplantation model

Abstract: Small‐for‐size syndrome (SFSS) has a poor prognosis due to excessive shear stress and sinusoidal microcirculatory disturbances in the acute phase after living‐donor liver transplantation (LDLT). Multilineage‐differentiating stress enduring (Muse) cells are reparative stem cells found in various tissues and currently under clinical trials. These cells selectively home to damaged sites via the sphingosine‐1‐phosphate (S1P)–S1P receptor 2 system and repair damaged tissue by pleiotropic effects, including tissue p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 58 publications
2
14
0
Order By: Relevance
“…Cell labeling offers great advantages of in vivo tracking and investigating the homing ability of transplanted cells by using noninvasive imaging techniques 33–36 . Transplanted LEPCs were labeled with the fluorescent lipophilic tracer DiR and imaged by IVIS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell labeling offers great advantages of in vivo tracking and investigating the homing ability of transplanted cells by using noninvasive imaging techniques 33–36 . Transplanted LEPCs were labeled with the fluorescent lipophilic tracer DiR and imaged by IVIS.…”
Section: Resultsmentioning
confidence: 99%
“…As Cell labeling offers great advantages of in vivo tracking and investigating the homing ability of transplanted cells by using noninvasive imaging techniques. [33][34][35][36] Transplanted LEPCs were labeled with the fluorescent lipophilic tracer DiR and imaged by IVIS. At 0 hour post-treatment, the cells were confined inside the spleen and then gradually moved into the liver.…”
Section: Overexpression Of Alr In Lepcs Promotes Hepatic Homingmentioning
confidence: 99%
“…Administering human bone marrow-derived MSCs and human bone marrow-derived Muse cells to a small-for-size rat model after liver transplantation showed that Muse cells migrated to the transplanted liver, and Ki-67-positive hepatocytes and sinusoidal endothelial cells were significantly higher in the Muse cell group. Furthermore, this study found that Muse cells could protect sinusoidal endothelial cells by expressing hepatocyte growth factor and vascular endothelial growth factor-A [ 25 ]. These studies suggest that Muse cells contribute to promoting liver function and regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…In the arts, a “muse” is a source of inspiration. In this issue of American Journal of Transplantation , Shono and colleagues were inspired by the cells lining the hepatic sinusoids to explore the use of muse cells—“multilineage‐differentiating, stress‐enduring” pluripotent‐like stem cells—to regrow these target cell populations in and improve outcomes using SFS grafts 4 . Muse cells reside endogenously in the bone marrow and peripheral blood as well as the connective tissue of nearly every organ.…”
Section: Figurementioning
confidence: 99%